HERMENEUTIKA HADIS ALA FAZLUR RAHMAN - Alma’arif, Alma’arif (Jurnal Studi Ilmu-ilmu Al-Qur'an dan Hadis, 2015)
"> Fazlur Rahman was a very famous Islamic reformer. He was from Pakistanwho previously had no contemporary thinkers such as Ahmad khan danSayyid Amir Ali and M. Iqbal. He mastered in turath and human sciencesin Islamic studies. On the understanding of hadith, Rahman had anidea that the need for reevaluation of the diverse elements in the hadithand reinterpretation of a comprehensive and holistic to the elements inaccordance with the moral - social conditions in the present. This can bedone by historical studies and the Qur’an as a reference. It supposes bedistinguished between the traditions of the historical and biography, thatthe traditions are supported by the facts of history, from technical traditionslargely historical, the traditions that are not supported by historical factsvalidity.